2003
DOI: 10.1002/jgm.440
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligodeoxynucleotide against HST‐1/FGF‐4 suppresses tumorigenicity of an orthotopic model for human germ cell tumor in nude mice

Abstract: Collectively, these results indicate that the antisense method against HST-1/FGF-4 gene expression will be a novel therapeutic approach for male germ cell tumors. The use of Atelocollagen-mediated administration of the antisense HST-1/FGF-4 ODNs may be useful in enhancing the effects of antisense therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…(52) To date, several reports have described that the potency of nucleic acid-based gene materials, such as plasmid DNA and antisense oligonucleotides, was greatly enhanced through the use of atelocollagen in vitro and in vivo. (24,(53)(54)(55) Recently, Takei et al reported that fluorescein-labeled and radiolabeled siRNA mixed with atelocollagen stabilized the tumors for at least 1 week, and intratumoral injection of atelocollagen in complex with siRNA against vascular endothelial growth factor showed dramatically suppressed tumor angiogenesis and tumor growth in a PC-3 sc xenograft model. (56) More recently, Takeshita et al reported that the systemic administration of atelocollagen in complex with siRNA targeting human enhancer of zeste homolog 2 into a mouse model of bone metastasis showed efficient inhibition of tumor growth without inducing any side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…(52) To date, several reports have described that the potency of nucleic acid-based gene materials, such as plasmid DNA and antisense oligonucleotides, was greatly enhanced through the use of atelocollagen in vitro and in vivo. (24,(53)(54)(55) Recently, Takei et al reported that fluorescein-labeled and radiolabeled siRNA mixed with atelocollagen stabilized the tumors for at least 1 week, and intratumoral injection of atelocollagen in complex with siRNA against vascular endothelial growth factor showed dramatically suppressed tumor angiogenesis and tumor growth in a PC-3 sc xenograft model. (56) More recently, Takeshita et al reported that the systemic administration of atelocollagen in complex with siRNA targeting human enhancer of zeste homolog 2 into a mouse model of bone metastasis showed efficient inhibition of tumor growth without inducing any side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in advanced prostate cancer, the sites most frequently affected by metastasis are the bones and regional lymph nodes. Patients with these metastases suffer pain and low limb edema, making it extremely important to explore avenues of treating such bone metastases.We previously demonstrated the efficacy of atelocollagen for delivery of nucleotides, such as plasmid DNA and antisense oligonucleotides, in vitro and in vivo (14)(15)(16)(17)(18)(19). Recently, we also reported that atelocollagen complexed with siRNA is resistant to nucleases and is efficiently transduced into cells, thereby allowing long-term gene silencing (20).…”
mentioning
confidence: 99%
“…Atelocollagen, which is prepared from bovine dermis, 17,18 contributes to increases in cellular uptake, nuclease resistance and the prolonged release of siRNA, 14,[19][20][21] as well as plasmid DNA, 17 and antisense oligonucleotide compounds, 10,11,13,22 administered to tumors. An siRNAatelocollagen complex also can be delivered via an intravenous injection route as nanoparticles, enabling systemic delivery of siRNAs.…”
mentioning
confidence: 99%